Displasia cleidocraneal - Reporte de caso - Alves, Nilton [UNESP]; Oliveira, Reinaldo de (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
The cleidocranial dysplasia is a rare disease which can occur either spontaneously or by a dominant autosomal inheritance, with no predilection of genre or ethnic group. The odontologist is, most of the times, the first professional who patients look for to solve the problem, since there is a delay in the eruption and /or an absence of permanent teeth. In the case related in this work, this was the reason why the patient looked for treatment. Many others odontological problems are also present in this syndrome, such as, supernumerary teeth, retained teeth, with shape deviation and absence of deciduous teeth resorption. The premature diagnosis allows a proper orientation for the treatment, offering a better life quality for the patient.
Cleidocranial dysplasia - A case report
Keywords: Cleidocranial dysplasia; Dentofacial deviation; Dysostosis